Soluble Aβ aggregates can inhibit prion propagation. Issue 11 (15th November 2017) - Sarell, Claire J.; Quarterman, Emma; Yip, Daniel C.-M.; Terry, Cassandra; Nicoll, Andrew J.; Wadsworth, Jonathan D. F.; Farrow, Mark A.; Walsh, Dominic M.; Collinge, John
Abstract : Abstract : Mammalian prions cause lethal neurodegenerative diseases such as Creutzfeldt–Jakob disease (CJD) and consist of multi-chain assemblies of misfolded cellular prion protein (PrP C ). Ligands that bind to PrP C can inhibit prion propagation and neurotoxicity. Extensive prior work established that certain soluble assemblies of the Alzheimer's disease (AD)-associated amyloid β-protein (Aβ) can tightly bind to PrP C, and that this interaction may be relevant to their toxicity in AD. Here, we investigated whether such soluble Aβ assemblies might, conversely, have an inhibitory effect on prion propagation. Using cellular models of prion infection and propagation and distinct Aβ preparations, we found that the form of Aβ assemblies which most avidly bound to PrP in vitro also inhibited prion infection and propagation. By contrast, forms of Aβ which exhibit little or no binding to PrP were unable to attenuate prion propagation. These data suggest that soluble aggregates of Aβ can compete with prions for binding to PrP C and emphasize the bidirectional nature of the interplay between Aβ and PrP C in Alzheimer's and prion diseases. Such inhibitory effects of Aβ on prion propagation may contribute to the apparent fall-off in the incidence of sporadic CJD at advanced age where cerebral Aβ deposition is common.